Estimates related to Caputo derivatives using generalized modified $ h $-convex functions - Benali, Halim; Souid, Mohammed Said; Günerhan, Hatıra; Fernandez-Gamiz, Unai (AIMS mathematics, 2024)
In the present work, we have established some new fractional integral inequalities for functions whose $ k $th-derivatives are generalized modified $ h $-convex and symmetric about the midpoint involving the Caputo fractional derivatives. Many particular cases are obtained by using the findings.